Use of Shear Wall and Reinforced Cement Concrete Bracing System Both in High Rise Commercial Buildings Using Staad Pro Software (International Journal of Innovative Research in Computer Science & Technology, 2022)
In earthquake prone zones the structures  are designed to withstand seismic or lateral forces along  with the gravity loads. In that respect shear wall system,  bracing system, diagrid etc., have been suggested over a  period of time. This study observed the combined  performance of shear wall and RCC bracing system, and  also the effect of their relative position in high rise  commercial building (G+10).The study aimed the  comparison of performance of shear wall and RCC bracing  system in high rise commercial buildings under seismic  loading. The total of 6 structural configurations viz.,  Moment resisting frame (Model 1), MRF stiffened with  RCC bracing system (Model 2), MRF stiffened with shear  wall system (Model 3), MRF stiffened with both shear wall  and RCC bracing system (Model 4A, Model 4B, and  Model 4C – Based on different relative location of shear  wall and RCC bracing system) were modelled and then  analysed. Analysis has been done in accordance with  1893:2002 using STAAD Pro V8i software. The post  analysis results concluded that The bracing system  improves not only the stiffness and strength capacity but  also the displacement capacity of the structure. And in  model 4( RCC X-bracing system is placed in similar way  as shear wall at corner 2 and 3) is more efficient, safe and  economical in earthquake as compared to other analysed  models.
Keywords: Stiffness; Strength, Bracing System; Shear wall System; Seismic zone v; IS 1893:2002 and STAAD -PRO v 8i